2002
DOI: 10.1021/jm020084h
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Opioid κ Receptor Selective Pure Antagonist from a Library of N-Substituted 4β-Methyl-5-(3-hydroxyphenyl)morphans

Abstract: A library of compounds biased toward opioid receptor antagonist activity was prepared by incorporating N-phenylpropyl-4beta-methyl-5-(3-hydroxyphenyl)morphans as the core scaffold using simultaneous solution phase synthetic methodology. From this library, N-phenylpropyl-4beta-methyl-5-(3-hydroxyphenyl)-7alpha-[3-(1-piperidinyl)propanamido]morphan [(-)-3b] was identified as the first potent and selective kappa opioid receptor antagonist from the 5-phenylmorphan class of opioids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 20 publications
5
34
0
Order By: Relevance
“…From a library of phenylmorphan scaffold, 7-[3-(1-piperidinyl)propanamido] morphan derivative (100) was identified as a potent and selective k opioid receptor antagonist. 176 The structure of this compound is similar to that of previously reported JDTic …”
Section: K-selective Agonists and Antagonistssupporting
confidence: 82%
“…From a library of phenylmorphan scaffold, 7-[3-(1-piperidinyl)propanamido] morphan derivative (100) was identified as a potent and selective k opioid receptor antagonist. 176 The structure of this compound is similar to that of previously reported JDTic …”
Section: K-selective Agonists and Antagonistssupporting
confidence: 82%
“…Moreover, 16 is also more potent at κ receptors (approximately 16-fold, K e = 220 nM vs K e = 3600 nM) and δ receptors (2-fold, K e = 950 nM vs K e = 1770 nM). A change in the C2 stereochemistry in 16 (17) decreased activity 7-fold at μ receptors (K e = 1500 nM vs K e = 210 nM) and 2-fold at δ receptors (K e = 1700 nM vs K e = 950 nM) compared to 15. This change also decreased activity 9-fold at κ receptors (K e = 1900 nM vs K e = 220 nM).…”
Section: Resultsmentioning
confidence: 97%
“…Such an interaction is consistent with our studies with κ selective 5-(3-hydroxyphenyl)morphans (4a, 27, and 28) where we found that the relative placement of the bridging ring and 4β-methyl group significantly impacted potency and selectivity for the κ receptor. 19,20 Another important aspect of the present study is that it adds additional support to the role of the trans-3,4-dimethyl structure or substructure that is essential for the antagonist activity of the trans-3,4-dimethyl-4-(3-hydroxyphenyl)piperidine (4) series, Figure 4. The 8a-methyl and the 5-position methylene of the bridging ring fulfill this role in the isoquinoline compounds 6a-g. Information as to the function of this and similar groups can be gleaned from the available literature.…”
Section: Discussionmentioning
confidence: 74%